2015
DOI: 10.1515/cjal-2015-0003
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Empirical Studies in L2 Dynamic Assessment

Abstract: The present paper reviews 25 studies conducted in the domain of L2 (second/foreign language) dynamic assessment (DA) in recent years. It begins with a survey of relevant research, then discusses some of the major findings and problems, and finishes with some suggestions for further research. The main findings of the review are as follows: (a) DA has the potential to promote L2 competence development; (b) both the interactionist approach and interventionist approach have attracted the interest of L2 researchers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…In the EFL and ESL language teaching, DA has received research interests. A majority of DA research in the field examines DA's potential in facilitating language development, by analyzing the effectiveness of two DA models (interactionist DA and Interventionist DA) in the development of language skills, such as listening, reading, speaking, writing, grammar and vocabulary (Li & Li, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…In the EFL and ESL language teaching, DA has received research interests. A majority of DA research in the field examines DA's potential in facilitating language development, by analyzing the effectiveness of two DA models (interactionist DA and Interventionist DA) in the development of language skills, such as listening, reading, speaking, writing, grammar and vocabulary (Li & Li, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…It can be indicated that external interventions to learners are introduced in the process of DA. Given its unique view on assessment and instruction, DA has received increasing interests in second and foreign language learning and teaching (Li & Li, 2015). DA is mainly studied in terms of its effectiveness of learners' language development in language sub-skills, such as listening and reading comprehension, grammar and vocabulary skills.…”
mentioning
confidence: 99%
“…Previous studies indicated that this sort of training that was embedded in direct interactions between the mediator and the student in DA process could bring about significant improvement in the students' language performance, especially in the group of students with learning disability or low proficiency (Law & Camilleri, 2007;Lidz, 1992;Martin, 2015;Pena, 2000;Swanson & Howard, 2005). Furthermore, it was also found in some research on DA that the positive results on the students' test scores after going through DA process increased the students' motivation to earn further achievement in their later performances (Haywood & Lidz, 2007;Li & Li, 2015;Pishghadam, Barabadi, & Kamrood, 2011;Zoghi & Malmeer, 2013).…”
Section: Expected Outcomementioning
confidence: 96%